MODALITY OF THE RESEARCH SEED AS AN EXTRACURRICULAR WORK IN UNIVERSITY TRAINING - Argota-Pérez, George (2023)
The purpose of the study was to describe the modality of the research hotbed as extracurricular work in university education. From June to September 2021, the research hotbed project "Formando y Formando" was carried out for teachers and students of the Universidad Nacional "San Luis Gonzaga", Ica, Peru. The academic areas that participated were: Pharmacy and Biochemistry, Environmental and Sanitary Engineering, as well as Dentistry where the students corresponded to the academic cycles of 1st, 6th and 8th. Three levels of training instructions were considered: 1st) identification of what to do, 2nd) execution of what to do and 3rd), communication of what to do. The research seedbed (SI) was carried out from the extracurricular work in university education (TEFU) through a development model that consisted of five instructions: title, introduction, objectives, measurement and proposed improvement according to the undesired situation. It was observed that upon completion of the TEFU development model in the SI, the students were able to complete the proposed activities, according to the planning where there was a demonstration of creative learning and team exchange. It is concluded that the hotbed of research as extracurricular work in university education allowed university students to acquire skills, academic commitment from their training and consolidate teamwork. Keywords: academic performance – extracurricular activity – hotbed of research – training